The Mediating Effect of Religiosity in Evaluating Individual Cultural Values Regarding Interest - Selim Aren; Hatice Nayman Hamamcı (Türkiye İslam İktisadı Dergisi)
This study aims to investigate the mediating role of religiosity on the relationship between individual cultural values and negative opinions on interest. In this way, we aim to obtain an empirical basis for theoretical knowledge and to provide a statistically greater explanation about negative opinions on interest and culture relations based on religiosity. In this context, data were collected between May 14 and June 1, 2020, in Turkey, a country where the majority of individuals are Muslim but Western values and synthesis of Eastern and Western cultures have been adopted. A total of 1.934 people participated in the survey. Exploratory factor analysis was performed on a newly developed scale measuring negative opinion on interest. Next, structural equation modeling (SEM) was used to test the research models and analyze the results from the confirmatory factor analysis. The analyses have determined individuals’ cultural values to be a determinant of their religiosity levels and these religiosity levels to increase alongside increases in collectivism, power distance, masculinity, and long-term orientation. In addition, positive and statistically significant relationships have been determined for collectivism, power distance, masculinity, and uncertainty avoidance orientations with negative opinions on interest. Findings have been obtained showing a negative and statistically significant relationship to exist between being long-term orientated and negative opinion on interest. As expected, the greater the religiosity level, the higher the negative opinion on interest. In addition, religiosity has also been reported to have a mediating effect on the relationship collectivism, power distance, masculinity, and negative opinion on interest have with interest.